2012
DOI: 10.1158/1055-9965.epi-12-0589
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prostate-Specific Antigen Concentration and Hemodilution among Chinese Middle-Aged Obese Men: A Hematocrit-Based Equation for Plasma Volume Estimation Is Induced

Abstract: Background: A hematocrit (HCT)-based and a body surface area (BSA)-based equations were applied for plasma volume (PV) estimation, respectively, to confirm and quantify the hemodilution effect in prostatespecific antigen (PSA) screening among obese men. The agreement between the equations was additionally investigated.Methods: A total of 1,444 men were retrospectively collected, with ages 40 to 65 years, PSA 0 to 4 ng/mL, and no prostate cancer. PSA mass was calculated as PSA concentration multiplied by PV. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Because of the absence of a plasma volume determined by "Golden criteria," we could not tell which equation is more suitable for clinical application. However, the discrepancies call for greater attention to further study on the problem (20). Second, because of the cross-sectional nature of the study, we cannot determine whether there is a causal or resultant relationship between the elevation of serum CEA and obesity.…”
Section: Discussionmentioning
confidence: 96%
“…Because of the absence of a plasma volume determined by "Golden criteria," we could not tell which equation is more suitable for clinical application. However, the discrepancies call for greater attention to further study on the problem (20). Second, because of the cross-sectional nature of the study, we cannot determine whether there is a causal or resultant relationship between the elevation of serum CEA and obesity.…”
Section: Discussionmentioning
confidence: 96%
“…These findings are corroborated by Banez et al who found that in three separate patient cohorts, obese men had similar or higher PSA mass [serum PSA concentration × total circulating plasma volume (estimated by body surface area)] compared to nonobese men. A subsequent study by Li et al utilized a hematocrit‐based and a body surface area‐based equation for estimating plasma volume to quantify PSA hemodilution. They found that for both models PSA mass remained consistent across increasing BMI categories.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, in the Asian area, studies on obesity and prostate cancer are less common than in the West . Because of the clearly differing features and body shape of Asian and Western people and as the definition of obesity is also different (obesity is defined as a BMI ≥ 25 kg/m 2 for Asian people and as ≥ 30 kg/m 2 for Western people ), there are many obstacles to making a generalized hypothesis and conducting studies.…”
Section: Discussionmentioning
confidence: 99%
“…In Asian countries, including Korea, despite the fact that there has been an explosion in both obesity and prostate cancer rates because of diets becoming Westernized and lifestyle changes [3, 12,13], studies on these subjects are less common than in the West, and the reported findings have been inconsistent [6,7,14,15]. Masuda et al [6] reported that obesity was associated with a higher risk of prostate cancer detection in a Japanese biopsy population.…”
Section: Introductionmentioning
confidence: 99%